Designing Blended Learning System with Realistic Mathematic Education for Vocational High School Students - Minarti Minarti; Lukman El Hakim (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Covid 19 pandemic has reached a new phase in Indonesia, necessitating the implementation of health standards across the board. One health regimen to prevent Covid 19 is blended learning, an alternative to combining indirect (online) and face-to-face (offline) learning. This research aims to give vocational students more flexibility in their education by developing a realistic mathematics education (RME) learning design for the area and volume of rotating objects. The research-and-development method was used for this work. This study focuses on high school students who are enrolled in vocational programmes. According to the findings of the need assessment and the student analysis, a random sample of participants provided the data. In order to improve education, it is indeed necessary to first assess both student demands and abilities. Discussed and modified to suit the pedagogical goals, performance targets, and learning results are analysed and compared. This research suggests that teachers learning about the surface area and volume of rotating objects would benefit from a blended learning design using the RME technique. This occurs when students are able to apply what they have learned to hypothetical situations that match the RME's criteria.